Oral health self-perception, maximum bite force and masticatory efficiency in patients with overdentures with different attachment systems—A crossover study - de Oliveira Lima, Amanda Laísa [UNESP]; Jabr, Camila Luiz [UNESP]; de Melo Rocha, Cibele Oliveira [UNESP]; Oliveira, Lucas Portela [UNESP]; de Oliveira Ribeiro, Rafael Antonio [UNESP]; de Assis Mollo Júnior, Francisco [UNESP]; Arioli Filho, João Neudenir [UNESP] (Wiley, 2024)
Background: The literature is unclear about how the different attachment systems for overdentures impact the maximum bite force, the masticatory efficiency and how this impact in the oral health self-perception in patients. Objective: To evaluate the effect of two attachment systems (O-ring and Locator) for mandibular overdenture using single implant on quality of life, maximum bite force (BF) and masticatory efficiency (ME). Methods: Twenty-eight completely edentulous denture wearers with a mandibular symphysis implant were randomly selected and allocated into two groups in a crossover study, considering O-ring and Locator attachment types. The quality of life and self-perception of oral health were assessed using the Oral Health Impact Profile (OHIP-Edent) and Geriatric Index of Determination of Oral Health (GOHAI) questionnaires, respectively. BF was measured using a gnathodynamometer and ME by chewing silicone cubes and almonds in different numbers of cycles. Results: There was no difference between the attachment systems about self-perceived oral health and impact on quality of life (p >.05). The O-ring-type system obtained a significantly higher BF than the locator-type system (p =.04). Regardless of the food chewed, no statistically significant difference was observed with the type of attachment (p >.05). The ME was directly proportional to the masticatory cycles only for almonds (p <.01). Conclusions: Locator and O-ring inserts had a similar impact on patients' quality of life, self-perception of oral health and ME. Additionally, the O-ring system exhibited superior properties in the BF.
Keywords: bite force; dental implantation; mastication; quality of life